Kepentingan dan Posisi Strategis Indonesia dalam Peta Geopolitik Indo-Pasifik - Nashir, Asep Kamaluddin (Intermestic: Journal of International Studies, 2024)
This writing aims to analyze the development of global geopolitics in the Indo-Pacific region. Furthermore, it focuses on analyzing Indonesia's maritime interests and strategic position in the region. Therefore, frameworks of geopolitical theory, international regimes, and maritime safety, security, and defense are needed as analytical tools. Findings in this writing explain that Indonesia has not yet directed its opportunities as an archipelagic state to enhance its role at the global level through the formation of international regimes to promote rules anchoring maritime safety, maritime security, and maritime defense despite the significant maritime interests in the Indo-Pacific. Moreover, developments in geopolitics in the region greatly influence Indonesia's maritime security. The results of this writing depict that maritime interests of archipelagic states must become a priority considering the geopolitical things have consequences in the maritime region for the future interests of the country.